Absolute lymphocyte count is an independent predictor of survival in patients with metastatic renal cell carcinoma treated with nivolumab. (5th October 2021) - Ueda, Kosuke; Suekane, Shigetaka; Kurose, Hirofumi; Ogasawara, Naoyuki; Hiroshige, Tasuku; Chikui, Katsuaki; Uemura, Keiichiro; Nakiri, Makoto; Nishihara, Kiyoaki; Matsuo, Mitsunori; Igawa, Tsukasa
Abstract: Objective: Programmed cell death-1 antibody therapy has demonstrated improved progression-free survival and overall survival in patients with metastatic renal cell carcinoma. However, there are limited studies on biomarkers that can predict the efficacy of immune checkpoint inhibitors. We examined the influence of peripheral inflammatory biomarkers on the clinical outcomes of patients with metastatic renal cell carcinoma treated with nivolumab. Methods: Data of 38 patients with metastatic renal cell carcinoma, who were treated with nivolumab monotherapy after receiving at least one molecular targeted therapy from November 2016 to February 2021, were retrospectively reviewed and analyzed. Results: Median progression-free survival and overall survival were significantly shorter in patients with low absolute lymphocyte count (<1300/μl) versus those with high absolute lymphocyte count (progression-free survival: P = 0.0102; overall survival: P = 0.0026). Median overall survival was shorter in patients with high neutrophil–lymphocyte ratio (≥3.0) versus those with low neutrophil–lymphocyte ratio ( P = 0.0344). Multivariate analysis showed that absolute lymphocyte count was an independent factor for progression-free survival (hazard ratio = 2.332, 95% confidence interval = 1.012–5.375, P = 0.0468) and overall survival (hazard ratio = 4.153, 95% confidence interval = 1.108–15.570, P = 0.0347). Increased absolute lymphocyte count, 1 month after nivolumab initiation, was a positive predictive factor for progression-free survival (hazard ratio = 0.419, 95% confidence interval = 0.189–0.926, P = 0.0317) and overall survival (hazard ratio = 0.285, 95% confidence interval = 0.091–0.890, P = 0.0308). Conclusion: Our study indicates that peripheral absolute lymphocyte count, before nivolumab initiation, is a predictor of poor response in metastatic renal cell carcinoma. Additionally, increased absolute lymphocyte count, 1 month post-nivolumab initiation, can be a predictor of the effects of nivolumab. Abstract : Peripheral absolute lymphocyte count, before nivolumab initiation, is an independent predictor of survival in metastatic renal cell carcinoma. Increased absolute lymphocyte count after initiation can be a predictor of nivolumab efficacy.